Intentional binding effect in children: insights from a new paradigm - Cavazzana, Annachiara; Begliomini, Chiara; Bisiacchi, Patrizia S. (Frontiers in Human Neuroscience, 2014)
Intentional binding (IB) refers to the temporal attraction between a voluntary action and its sensory consequence. Since its discovery in 2002, it has been considered to be a valid implicit measure of sense of agency (SoA), since it only occurs in the context of voluntary actions. The vast majority of studies considering IB have recruited young adults as participants, while neglecting possible age-related differences. The aim of the present work is to study the development of IB in ten-year-old children. In place of Libet’s classical clock method, we decided to implement a new and more suitable paradigm in order to study IB, since children could have some difficulties in dealing with reading clocks. A stream of unpredictable letters was therefore used: participants had to remember which letter was on the screen when they made a voluntary action, heard a sound, or felt their right index finger moved down passively. In Experiment I, a group of young adults was tested in order to replicate the IB effect with this new paradigm. In Experiment II, the same paradigm was then administered to children in order to investigate whether such an effect has already emerged at this age. The data from Experiment I showed the presence of the IB effect in adults. However, Experiment II demonstrated a clear reduction of IB. The comparison of the two groups revealed that the young adult group differed from the children, showing a significantly stronger linkage between actions and their consequences. The results indicate a developmental trend in the IB effect. This finding is discussed in light of the maturation process of the frontal cortical network.